(untitled) (UNED Research Journal, 2017)
Fertilizers are essential for agriculture but can produce contamination with heavy metals and affect the health of humans and farm animals. Reliable methods to measure these metals are important.We evaluated the recovery of the analytical method employed in a services laboratory in Costa Rica for the quantification of nickel, chromium, cadmium, lead, arsenic, selenium and mercury in fertilizers. A phosphate and a nitrogenous matrix were studied separately, enriched at three concentration levels within the working range, to establish the accuracy of the analysis procedure based on AOAC for the validation of analytical methods (80- 110%). In the quantitative study both cadmium and chromium for the two matrices presented optimum results from the point of view of recovery; lead also had positive accuracy (except at low concentration). On the other hand, nickel in the phosphate matrix was slightly above the maximum permissible limit, but not the nitrogen, Finally in the metals arsenic, selenium and mercury there was no recovery for both samples using the established procedure.